IMPLEMENTASI PEMBELAJARAN PROJECT BASE LERNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI LETAK GEOGRAFIS KELAS 5 SDN SAWOJAJAR 1 KOTA MALANG - Danang Saputra; Maharani Putri Kumalasani; Rini Wasitah (STKIP Subang, 2023)
The learning outcomes of grade 5 students at SDN Sawojajar 1 in the learning process on geographical location material are still low. The cause of the lack of learning processes experienced by these students is because they have not been managed properly, the point is to improve learning outcomes and student learning creativity in applying effective media providing an alternative to research using classroom action research learning methods. The purpose of this classroom action research is research that is used to improve the learning process as an effort to improve learning outcomes and learning creativity of 5th grade students at SDN Sawojajar 1. This classroom action research takes place in two cycles, each cycle consisting of 4 steps of research activities, namely planning, implementing, observation and reflection which are used as a basis for improving planning in the next cycle. the instruments used to observe the results of these actions are a practical procedure based on projects, questionnaires and tests of student learning outcomes. Based on the results of data analysis in cycles 1 and 2, students' creativity increased in study groups as well as student learning outcomes in study groups. the results of the analysis of cycles 1 and 2, as well as the learning outcomes of students' scores have reached the predetermined minimum completeness criteria, namely 75. The average value of student learning outcomes in objects in cycle 1 increased from 36% to 75% in cycle 2.